2017
DOI: 10.5380/rsa.v18i4.54203
|View full text |Cite
|
Sign up to set email alerts
|

Influência De Diferentes Fontes De Matéria Orgânica Na Propagação Da Schinus Terebinthifolius Raddi

Abstract: Resumo -A recuperação de ecossistemas degradados pode não ocorrer da maneira desejada se houver carência nutricional ou suprimento insuficiente de nutrientes durante o estádio inicial de desenvolvimento. Portanto, o uso da matéria orgânica se torna essencial nesta etapa inicial de desenvolvimento. O objetivo desse trabalho foi avaliar o desenvolvimento e a qualidade de mudas de aroeira-vermelha em função de substratos contendo diferentes fontes de matéria orgânica. O experimento foi realizado em casa de vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In relation to the leaf area ( Figure 1A), the estimated value obtained with the addition of 80% of tannery sludge in the substrate was 2.5 cm². The leaf area is a fundamental component for plants, since the larger is the leaf area, the greater the light uptake by the plant and the greater the production of metabolic energy, which will be responsible for the maintenance of plant metabolism and growth, as well as in determining the productivity of the plant (Koester et al, 2014;Sales et al, 2017). Sales et al (2018c) studying chlorophyll content in Schinus terebinthifolius Raddi seedlings cultivated in different substrates, showed that the addition of tannery sludge in the substrate positively favors chlorophyll content, as well as other organic materials added in other compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the leaf area ( Figure 1A), the estimated value obtained with the addition of 80% of tannery sludge in the substrate was 2.5 cm². The leaf area is a fundamental component for plants, since the larger is the leaf area, the greater the light uptake by the plant and the greater the production of metabolic energy, which will be responsible for the maintenance of plant metabolism and growth, as well as in determining the productivity of the plant (Koester et al, 2014;Sales et al, 2017). Sales et al (2018c) studying chlorophyll content in Schinus terebinthifolius Raddi seedlings cultivated in different substrates, showed that the addition of tannery sludge in the substrate positively favors chlorophyll content, as well as other organic materials added in other compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Sales et al (2018c) studying chlorophyll content in Schinus terebinthifolius Raddi seedlings cultivated in different substrates, showed that the addition of tannery sludge in the substrate positively favors chlorophyll content, as well as other organic materials added in other compounds. The higher organic matter content and nutrients of these substrates may result in higher chlorophyll production and cellular structures, resulting in a larger leaf area (Sales et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2 established the minimum value for the IQD was 0.20 which is a good indicator of cutting quali general, therefore, in this study, results were found to be higher than the minimum index established by Hunt. Sales et al [25] studied the…”
Section: Root Dry Matter Mass (Rdm) (A) Shoot Dry Matter Mass (Sdm) (B) Total Dry Matter Mass (Tdm) (C) and Dickson's Quality Index (Iqd)mentioning
confidence: 99%
“…Hunt [24] established the minimum value for the IQD was 0.20 which is a good indicator of cutting quality in general, therefore, in this study, results were found to be higher than the minimum index . [25] studied the effect of different sources of organic matter in the propagation of Schinus terebentifolia where they found IQD values that varied from 0.01 to 0.32 in plants after 121 days.…”
Section: Nitrogen Balance (Nbi_g + Nbi_r) (A) Flavonoids (B) Total Chlorophyll (Sfr_g + Sfr_r) (C) and Spad Index Of Plants Produced Withmentioning
confidence: 99%